MODEL DAKWAH SOSIAL KEAGAMAAN PESANTREN MELALUI PROGRAM SAFARI RAMADHAN - Lilik Mutaharoh; Muhammad Ullin Nuha (Pascasarjana Universitas Al-Qolam Malang, 2026)
This study comprehensively examines the socio-religious da'wah model through the Ramadan Safari program by the Lirboyo Islamic Boarding School in North Kotabumi District, North Lampung. The research uses a qualitative approach with the type of field research, with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. The focus of this research is to analyze da'wah strategies, implementation processes, and their impact on the socio-religious life of heterogeneous communities. The results of the study show that the effectiveness of da'wah is not only determined by the delivery of religious materials, but also by communicative and adaptive social approaches (mu'asyarah). The students are able to integrate Islamic knowledge with the social reality of the community so that da'wah is applicable and responsive to the needs of the community. The internalization of the values of Ahlussunnah Wal Jama'ah An-Nahdliyah such as tawassuth, tasamuh, and tawazun, as well as the strengthening of the Islamic paradigm as a blessing for all nature, plays a role in building religious moderation. This program has a real impact in the form of increasing religious activities, changing people's behavior towards a better religious life, and increasing trust in Islamic boarding schools. Thus, Safari Ramadan can be a relevant socio-religious model of da'wah to strengthen spiritual and social stability in a multicultural society.